Simple assay quantifying sediment resuspension effects on marine carbon storage - Ines Bartl; Tegan Evans; Jenny Hillman; Simon Thrush (Methods in Ecology and Evolution)
Abstract The seafloor plays a vital role in Earth's climate by storing carbon. However, human activities that disturb the seafloor undermine this function and receive little regulatory attention. This oversight is often due to a lack of empirical data linked to low sampling resolution of the heterogeneous seafloor, highlighting the need for a simple, fast, reproducible quantification approach. We address this gap by presenting a simple sediment resuspension assay that allows highly replicated sampling of heterogeneous sediments, quantifying the immediate impact on organic carbon mineralization. It is based on biochemical oxygen demand and compares sediment oxygen demand between undisturbed sediment cores and those subjected to resuspension, estimating resuspension‐induced CO₂ production. Oxygen demand in the resuspension treatment was 2.4–13.4 times higher than in the undisturbed cores, resulting in resuspension‐induced CO₂ production of 210–2064 μmol CO₂ m−2 h−1. This immediate resuspension effect on organic carbon mineralization suggests a substantial impact on organic C stocks that could otherwise contribute to carbon sequestration. Our assay is notable for its simplicity and accessibility. It offers a critical step towards a more accurate large‐scale assessment of sediment resuspension impacts across the heterogeneous seafloor, evaluating its vulnerability to disturbance and the role of demersal fishing in exacerbating climate change.